The impact of remdesivir on renal and liver functions in severe COVID-19 patients with presence of viral load - Petr Waldauf; Ivana Jurisinova; Eva Svobodova; Michaela Diblickova; Tomas Tencer; Jan Zavora; Gabriela Smela; Lenka Kupidlovska; Vaclava Adamkova; Marta Fridrichova; Karolina Jerabkova; Jakub Mikes; et al. (Scientific Reports)
Abstract The impact of remdesivir on renal and liver functions remains a matter of concern in advanced COVID-19 patients with high illness severity and presence of viral load. The laboratory results of the 114 patients (males 55.8%, age 71 (59; 77) years) with a detectable viral load treated with remdesivir were compared with the controls. Baseline plasmatic creatinine (PCr) < 150 µmol/l in patients on remdesivir decreased equally to controls (− 6 (− 20; 9) vs. − 8 (− 24; 2) µmol/l, n = 170, p = 0.11). The similar trends were found for baseline PCr ≥ 150 µmol/l (− 57 (− 129; − 15) µmol/l for remdesivir group vs. − 65 (− 111; − 7) µmol/l, p > 0.9). Changes of PCr were independent of the remdesivir therapy, the statistically significant confounders were baseline PCr levels (p < 0.001), hospital length-of-stay (p < 0.001), leukocyte-to-lymphocyte ratio (p = 0.025). The plasmatic urea (PU) mildly increased in the remdesivir group (1 (− 2; 5) mmol/l vs. 0 (− 3; 2) mmol/l in the controls, p = 0.009), its levels were related to remdesivir (p = 0.026), age (p = 0.002), PCr (p < 0.001), hospital length-of-stay (p < 0.001), IPPV (p = 0.035). Regarding the liver function tests the significant relationships to remdesivir therapy were found only for GGT (p = 0.007) and ALT (p = 0.044). The levels of PCr were decreasing over the hospitalisation period including patients with mild-to-moderate renal insufficiency. The multivariate regression analysis excluded an impact of remdesivir on the PCr changes yet admitted an impact on the levels of urea, GGT and ALT.